FORMULASI SEDIAAN GEL MASKER WAJAH DARI BAHAN ALAM EKSTRAK RIMPANG TEMU MANGGA(Curcumaamada) - Maringan, Maringan; Sitorus, Erly Nurita; Thaib, Cut Masyithah; Afrilla, Cut Windy (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
Temu manggais a plantthat has a highantioxidant content. One type of antioxidant in temu manggais vitamin E which can rejuvenate the skin. There are manyuseful ingredients in the temu mangorhizome, namel ycurcumin, flavonoids, tannins, saponinsandes sential oils. This research method was carried out experimentally. The temu mangga rhizomewas extractedusing 70% ethanolsolventbymaceration method then concentrate dusing a rotary evaporator. The extractof temu mangga rhizome was then formulate dinto a gel maskwith a concentrationof F0 as a blank, using a base gel mask without extractand with the addition of F1 (1%) and F2 (3%) extracts. Evaluationof gel mask preparations includesorganoleptictests, namely observing with the five human sensessuch as odor, color, shape, pH test, homogeneity, dryingtimetest, irritationtest, and effectiveness test as a facial moisturizer using a skin analyzeron the facial skin of volunteers. Parameters measured include moisturecontent, poresize, and wrinkles. The resultsof this study indicate that the gel maskpreparation has a drying time of 20-30 minutes, isstablefor 4 weeks of storage anddoes not irritatethe skin. The measure mentresults of facial moisturizing activity showed that 3% extra gel mask was the best by increasing water content, shrinkingporeson facial skin and reducing wrinkleson the face